Curating as Branding: Crafting Institutional Image through Exhibition Cipta! Kapita Selekta Cikini Raya 73 - Nugeraha, Ady (Universitas Multimedia Nusantara, 2025)
This paper examines how curatorial practice can function as a form of institutional branding, using the exhibition Cipta! Kapita Selekta Cikini Raya 73 as a case study. Situated within the revitalized Taman Ismail Marzuki arts complex, the exhibition foregrounded archival materials, canonical artworks, and diverse artistic voices to narrate the institution’s historical and cultural significance. Drawing from practice-based research and curatorial reflection, this study analyzes curatorial choices including thematic grouping, exhibition texts, and spatial design through a branding framework that identifies symbolic codes such as memory, representation, heritage, and participation. The findings demonstrate that curatorial strategies extend beyond aesthetic presentation to construct institutional narratives, reinforce symbolic authority, and shape public perception. By mapping curatorial strategies to branding codes, this paper argues that exhibitions can operate as a soft branding mechanism, positioning cultural institutions as key agents in defining cultural identity and meaning.